Photoperiodic regulation of FGF21 production in the Siberian hamster - Samms, Ricardo J.; Fowler, Maxine J.; Cooper, Scott; Emmerson, Paul; Coskun, Tamer; Adams, Andrew C.; Kharitonenkov, Alexei; Tsintzas, Kostas; Ebling, Francis J.P. (Elsevier, 2014)
FGF21 is an endocrine member of the fibroblast growth factor superfamily that has been shown to play an important role in the physiological response to nutrient deprivation. Food restriction enhances hepatic FGF21 production, which serves to engage an integrated response to energy deficit. Specifically, elevated FGF21 levels lead to reduced gluconeogenesis and increased hepatic ketogenesis. However, circulating FGF21 concentrations also paradoxically rise in states of metabolic dysfunction such as obesity. Furthermore, multiple peripheral tissues also produce FGF21 in addition to the liver, raising questions as to its endocrine and paracrine roles in the control of energy metabolism. The objectives of this study were to measure plasma FGF21 concentrations in the Siberian hamster, a rodent which undergoes a seasonal cycle of fattening and body weight gain in the long days (LD) of summer, followed by reduction of appetite and fat catabolism in the short days (SD) of winter. Groups of adult male hamsters were raised in long days, and then exposed to SD for up to 12 weeks. Chronic exposure of LD animals to SD led to a significant increase in circulating FGF21 concentrations. This elevation of circulating FGF21 was preceded by an increase in liver FGF21 protein production evident as early as 4 weeks of exposure to SD. FGF21 protein abundance was also increased significantly in interscapular brown adipose tissue, with a positive correlation between plasma levels of FGF21 and BAT protein abundance throughout the experimental period. Epididymal white adipose tissue and skeletal muscle (gastrocnemius) also produced FGF21, but levels did not change in response to a change in photoperiod. In summary, a natural programmed state of fat catabolism was associated with increased FGF21 production in the liver and BAT, consistent with the view that FGF21 has a role in adapting hamsters to the hypophagic winter state.